Pengaruh Social Media Marketing Fintech, Fintech Knowledge, Dan Gaya Hidup Konsumtif Terhadap Minat Penggunaan Pinjaman Online P2P Lending - Rohmah, Nabila Alfiyatu; Susyanti, Jeni; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study examines a phenomenon, namely the influence of Social Media Marketing Fintech, Fintech Knowledge, and consumptive lifestyles on interest in making P2P Lending online loans. The increase in online loans favoured by the community, spreading to students, provides an exciting issue to be studied in this study. Students at a productive age have many advantages from easy access to the internet world, namely with the social media they have, making information readily available. Sources of knowledge can also be taken in various ways. Still, students' interest is weak in the world of literacy, making knowledge about the world of online loans overlap, coupled with the lifestyle of today's students with a wasteful lifestyle. The total population for this study consisted of 2288 student of University of Islam Malang, and a purposive sampling technique was employed, resulting in a sample size 70 students. The data collected was analyzed using multiple linear regression. The result of this research concludes a positive and significant influence of social media marketing fintech and fintech knowledge and a substantial effect on consumptive lifestyles and interest in using online loans.The results of the partial test prove that social media marketing influences interest in using online loans, fontech knowledge partially influences interest in using online loans, and lifestyle also partially influences interest in using online loans  Keywords: P2P Lending, fintech, student, online loans, lifestyle, fintech knowledge